Chip PCR. II. Investigation of different PCR amplification systems in microbabricated silicon-glass chips. - Cheng, J (1996)
We examined PCR in silicon dioxide-coated silicon-glass chips (12 microl in volume with a surface to volume ratio of approximately 17.5 mm(2)/microl) using two PCR reagent systems: (i) the conventional reagent system using Taq DNA polymerase; (ii) the hot-start reagent system based on a mixture of TaqStart antibody and Taq DNA polymerase. Quantitative results obtained from capillary electrophoresis for the expected amplification products showed that amplification in microchips was reproducible (between batch coefficient of variation 7.71%) and provided excellent yields. We also used the chip for PCR directly from isolated intact human lymphocytes. The amplification results were comparable with those obtained using extracted human genomic DNA. This investigation is fundamental to the integration of sample preparation, polynucleotide amplification and amplicate detection on a microchip.